A new species of Wuliphantes from Sichuan, China, with re-description on the type specimens of W. tongluensis (Araneae, Linyphiidae) - Lan Yang; Zhiyuan Yao; Shuqiang Li (Biodiversity Data Journal, 2023)
The genus Wuliphantes Irfan, Wang & Zhang, 2023 is a small genus in the family Linyphiidae Blackwall, 1859, with only three species: W. guanshan (Irfan, Wang & Zhang, 2022), W. tongluensis (Chen & Song, 1988) and W. trigyrus Irfan, Wang & Zhang, 2023, all distributed in China.A new species: Wuliphantes yaan sp. nov. from Sichuan Province, China is reported. In addition, we re-described the type specimens of W. tongluensis (Chen & Song, 1988) that is similar to W. yaan sp. nov.